2009
DOI: 10.2147/opth.s3228
|View full text |Cite
|
Sign up to set email alerts
|

Latanoprost ophthalmic solution in the treatment of open angle glaucoma or raised intraocular pressure: a review

Abstract: Latanoprost is a prostaglandin F2-alpha isopropyl ester prodrug which is rapidly hydrolyzed by esterases in the cornea to the biologically active latanoprost acid. When latanoprost is topically administered into the eye, the cornea seems to act like as a slow-release depot to the anterior segment. One hour after administration maximum concentration is found in the iris, followed by the anterior chamber and the ciliary body. Despite extensive research, controversy remains about the real mechanism of action of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…In view of the suggestion of setting a more comprehensive management target regarding patients' 24-hour IOP profiles, we have also discussed the effectiveness of glaucomatous medications, laser trabeculoplasty, and trabeculectomy in optimizing various 24-hour IOP parameters. According to current data, prostaglandin analogues (especially bimatoprost and travoprost [51, 85]) were the most effective topical eyedrops to achieve a uniform 24-hour IOP reduction [8386], and they were also effective in reducing the maximum and minimum IOP and short-term IOP fluctuations [87]. In particular, evening administration of prostaglandin analogues was shown to be better than morning dosing to lower daytime IOP in patients with POAG [19, 81, 83, 92].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the suggestion of setting a more comprehensive management target regarding patients' 24-hour IOP profiles, we have also discussed the effectiveness of glaucomatous medications, laser trabeculoplasty, and trabeculectomy in optimizing various 24-hour IOP parameters. According to current data, prostaglandin analogues (especially bimatoprost and travoprost [51, 85]) were the most effective topical eyedrops to achieve a uniform 24-hour IOP reduction [8386], and they were also effective in reducing the maximum and minimum IOP and short-term IOP fluctuations [87]. In particular, evening administration of prostaglandin analogues was shown to be better than morning dosing to lower daytime IOP in patients with POAG [19, 81, 83, 92].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin analogues (travoprost, latanoprost, bimatoprost, tafluprost) are the most potent topical antiglaucoma agents which can achieve uniform 24-hour IOP reduction of 24–29% [8386]. Stewart et al conducted a meta-analysis of studies that assessed the 24-hour efficacy of antiglaucoma medications and concluded that bimatoprost followed by travoprost were the two most effective IOP-reducing medications [51, 85].…”
Section: Therapeutic Efficacy Of Current Glaucoma Management Modalmentioning
confidence: 99%
“…пролекарство) кислоты латанопроста, который является аналогом PGF 2α. Латанопрост гидролизуется эстеразой роговицы с образованием биологически активного вещества латанопростовой кислоты [11]. Свободная гидрофильная кислота латанопроста обладает низкой тропностью к простаноидным рецепторам, отвечающим за воспалительные реакции, и высокую тропность к рецепторам, обеспечивающим снижение внутриглазного давления (ВГД), что указывает на высокую селективность препарата [12,13].…”
Section: история терапии глаукомыunclassified